Evaluation of bronchial asthma educational package on asthma self-management among school age children based on Orem’s self-care model in Zagazig city - Mersal, Fathia; El-Awady, Samah (International Journal of Advanced Nursing Studies, 2017)
Background: Asthma is the widespread health problem and most common chronic disease among children. Developing self-care skills related to children with asthma forms a basis for nursing care. Orem’s self-care model is one of the most comprehensive self-care theories that provide a good clinical guide for planning and implementing the principles of good self-care.The Aim of this study: was to determine the effect of asthma educational package based on Orem’s self-care model on the development of self-care activities of children with asthma.Subjects and Methods: a quasi-experimental study conducted on a purposive sample of 106 children with bronchial asthma in pediatric outpatient clinic at Zagazig University hospital. The research tools used in this study were demographic characteristics of studied children. Asthma triggers inventory, asthma knowledge questionnaire, asthma self-management questionnaire, asthma Self-Efficacy regarding self-management of asthma, medication adherence, and inhaler technique observation checklist and health instruction guidelines.Results: the results showed that after the training intervention self-efficacy, asthma management, adherence of asthmatic children to medications were significantly increased (p > 000). The study findings concluded that the asthma education program improved all aspects of self-efficacy and activities of asthma management after program implementation.Conclusion: the educational program based on Orem’s self-care model successfully improves the performance of inhaler use. The study indicates that self-care activities were efficient among children with asthma after implementation of program.Recommendations: it suggested to conduct Orem’s self-care model for children with bronchial asthma and to replicate the study in many settings to support its effectiveness.